Persepsi Pengurus Terhadap Faktor-Faktor Yang Mempengaruhi Coaching Dalam Organisasi Perhotelan - Nur A'fini, Ro'aini (Universiti Malaysia Sarawak (UNIMAS), 2002)
The purpose of this study is to identify the perception of managers about the factors that influence coaching in an organization. This study also aims to identify the correlation between the perception of the managers and the factors that influence coaching which are competence that must managers have as a coach factor, coaching as a tool of self and career development factor, and barriers in coaching factor. A set of questionnaire was used as a research instrument and then was distributed to 30 managers in the hotel organizations around Kuching. The finding has been analyzed by using SPSS 10.05 and Spearman Correlation Analysis is use to identify the significant correlation between the perception of managers and the factors. The finding of the study indicated that 96.7% of respondents obtained positive perception towards coaching. Barriers in coaching factors were found to have a positive significant correlation with the perception of managers with rs=366. On the other hand, for competence that managers must have as a coach factor and coaching as a tool of self and career development factor have no correlation with perception of managers. Hence, it is suggested that organizations should identify the competence that managers should have as coach in the coaching program and coaching program should be implemented frequently to develop individual or group. In addition, organizations should identify the resistance in coaching before it is conducted in the organization.